Suku Bakumpai, Sebuah Pergulatan Identitas antara Dayak dan Melayu Sebuah Tinjauan Budaya dan Linguistik - Qalyubi, Imam Qalyubi (Jurnal Studi Agama dan Masyarakat, 2012)
This discussion refers to the classification made by Mallinckrodt (1928) an anthropologist as well as a Dutch colonial controller, who stated that the native of inhabitant of Borneo is the Dayak non-Muslims. This statement developed into the hot issue among researchers, and the linguist in particular, mainly after the independence.To identify the objectivity of the Mallinckrodt statement, this study tried to examine from the standpoint of linguistic science and other aspects, such as the identity markers inherited from the earlier by the Indonesian ancestors before the arrival of the colonialists.After identifying all of the facts in linguistic, cultural and social facts in Bakumpai society, can be concluded that the Mallinckrodt tesis, which is stated that the native of inhabitant of Borneo is the Dayak non-Muslims finally in this research found the different evidents. By using the comparative linguistics and synchronic that is conducted on Ngaju, Bakumpai and Banjar language either in Marabahan Bakumpai, explicitly that Bakumpai language is derived from Sub-Ngaju Dayak dialects. Thus,Â  in general conclusions that the language that is spoken in Marabahan is Bakumpai Dayak language and automatically, the speakers are also a part of the Dayak tribe. This case is refers to "The language is the nations identity.Â